Konsep Lingkungan Pendidikan Dalam Al-Qur’an: Analisis Tafsir Tarbawi Pada Ayat-Ayat Tarbiyah - Siti Mashitoh; Iqlimatul Fajriyah; Atabik Luthfi; Marhadi Muhayar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the concept of the educational environment in the Qur’an through a tarbawi interpretative approach to selected tarbiyah verses. The educational environment plays a significant role in shaping learners’ personality, morality, and spirituality within Islamic education. This research employs a qualitative library research method. Primary data consist of Qur’anic verses related to education and classical as well as contemporary tarbawi exegeses, while secondary data are drawn from Islamic education literature. Data were analyzed using thematic content analysis. The findings reveal that the Qur’an offers a comprehensive framework of the educational environment encompassing three interconnected dimensions: family, school, and social environment. These environments collectively function as foundational spaces for the internalization of Islamic values and character development. This study highlights that a Qur’anic-based understanding of the educational environment provides important conceptual and practical implications for developing holistic, value-oriented, and contextually relevant Islamic education in contemporary society.